2011
DOI: 10.1017/jfm.2011.333
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of particle segregation in homogeneous isotropic turbulence

Abstract: A full Lagrangian method (FLM) is used in direct numerical simulations (DNS) of incompressible homogeneous isotropic and statistically stationary turbulent flow to measure the statistical properties of the segregation of small inertial particles advected with Stokes drag by the flow. Qualitative good agreement is observed with previous kinematic simulations (KS) (IJzermans, Meneguz & Reeks, J. Fluid Mech., vol. 653, 2010, pp. 99–136): in particular, the existence of singularities in the particle concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 21 publications
4
54
0
Order By: Relevance
“…As the particles cluster onto a network of caustic lines (analogous to the networks of optical caustics that can be seen on the bottom of a swimming pool) this process can facilitate coagulation of particles by bringing them into close proximity, even in cases where the trajectories do not coalesce Mehlig 2005, Wilkinson et al 2007). This model of particle segregation in homogeneous isotropic turbulence was confirmed by Meneguz and Reeks (2011), who amongst other things identified an interesting threshold value for the particle Stokes number above which the net compressibility of the particle concentration changes sign (from compression to dilation). All these processes are important influences on particle agglomeration and play a crucial role in (terrestrial) atmospheric phenomena such as droplet formation in turbulent clouds , Devenish et al 2012).…”
Section: The Notion Of "Vorticity" and Its Role In Particle Dynamicssupporting
confidence: 52%
“…As the particles cluster onto a network of caustic lines (analogous to the networks of optical caustics that can be seen on the bottom of a swimming pool) this process can facilitate coagulation of particles by bringing them into close proximity, even in cases where the trajectories do not coalesce Mehlig 2005, Wilkinson et al 2007). This model of particle segregation in homogeneous isotropic turbulence was confirmed by Meneguz and Reeks (2011), who amongst other things identified an interesting threshold value for the particle Stokes number above which the net compressibility of the particle concentration changes sign (from compression to dilation). All these processes are important influences on particle agglomeration and play a crucial role in (terrestrial) atmospheric phenomena such as droplet formation in turbulent clouds , Devenish et al 2012).…”
Section: The Notion Of "Vorticity" and Its Role In Particle Dynamicssupporting
confidence: 52%
“…We show that as det J approaches zero, Tr Z → −∞. We briefly comment on the statistical properties of the singularities (Meneguz and Reeks 2011).…”
Section: Introductionmentioning
confidence: 86%
“…The modes are chosen in such a way that the associated energy spectrum approximates a prescribed form, namely that originally used by Kraichnan (1970). The model is identical to that used by IJzermans et al (2010) and Meneguz and Reeks (2011). For convenience, we briefly summarize its relevant features below.…”
Section: Kinematic Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamical systems theory has been applied to the motion of particles, first by Sommerer and Ott 15 and in turbulent flows by Bec 16 and Wilkinson et al 17 who showed that periods in time exist where particle trajectories may cross leading to particle collisions. Relaxing an assumption of Wilkinson et al, 17 that the typical correlation time of the carrier flow is small, Reeks and co-workers have deployed the full Lagrangian method (FLM) of Ostiptsov 18 first in synthetic flows 19 and recently in isotropic turbulence 20 to quantify non-uniformities and singularities in the spatial distribution of particles more generally. The advantage of FLM being that the analysis takes place on infinitesimally small scales and does not rely on defining a box size for counting purposes and that a small Stokes number limit is not implicit in the method.…”
Section: Introductionmentioning
confidence: 99%